THE TRANSITION FROM VICTORIAN TO MODERN LITERATURE: THOMAS HARDY AND HENRY JAMES (Ustozlar uchun, 2025)
The transition from Victorian to Modern English literature marked a fundamental shift in literary style, worldview, and narrative techniques. This article examines how Thomas Hardy and Henry James—two central figures at the turn of the 20th century—embody this transformation. Hardy preserved Victorian concerns such as morality, determinism, and society’s constraints, yet introduced darker realism and pessimism that foreshadow modernist ideas. Henry James, in contrast, advanced psychological depth, interiority, and innovative narrative perspectives, establishing foundations for modern fiction. Through comparative analysis, this paper highlights how both writers bridged two eras, influencing the emergence of 20th-century modernism.